Pengembangan Sistem Informasi Akuntansi Berbasis Aplikasi : Studi Kasus Pada PT. Putra Bungsu Irdani Jambi - Satria Bahar Hidayat; Havis Taufik S; Aditya Pradana; Indah Mutiara (Jurnal Akuntan Publik, 2025)
This study aims to develop an application-based accounting information system applied to developers in Jambi City, the phenomenon that occurs now is recording financial statements still using manual methods or even using a simple application, namely Microsoft Excel only. In the era of technology that has been very rapidly developed and has not been utilized in its application. Types of qualitative research. This research uses qualitative research design with a case study approach. The qualitative approach was chosen because it allows researchers to gain a deep understanding of the development of accounting information systems at PT Putra Bungsu Irdani Jambi.